2006
DOI: 10.1007/s10329-006-0192-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Assamese macaques (Macaca assamensis) in the Inner Himalayan region of Bhutan and their mtDNA diversity

Abstract: The distributions of Assamese macaques (Macaca assamensis) and rhesus macaques (M. mulatta) in Bhutan have been only partially documented. In order to investigate the distribution patterns of these species, we conducted field observation and genetic assessment with mitochondrial DNA (mtDNA) typing of macaques in the Inner Himalayas of Bhutan. There were 24 sightings of macaque groups, and all were visually identified as Assamese macaques. No groups of rhesus macaques were sighted in this survey area, in contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
2
10
1
Order By: Relevance
“…This species has been reported from Nepal, India (Medhi et al, 2007), Bhutan (Kawamoto et al, 2006) Myanmar, Bangladesh (Menon, 2003;Chalise, 2011) Thailand, Southernmost China and Laos (Zhou et al, 2011;Timmins & Duckworth, 2013). It was recorded from North Thailand ranging 610m to 1830m asl (Sanjaya et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This species has been reported from Nepal, India (Medhi et al, 2007), Bhutan (Kawamoto et al, 2006) Myanmar, Bangladesh (Menon, 2003;Chalise, 2011) Thailand, Southernmost China and Laos (Zhou et al, 2011;Timmins & Duckworth, 2013). It was recorded from North Thailand ranging 610m to 1830m asl (Sanjaya et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2013). Besides Nepal, this species has been reported from India (Medhi et al 2007), Bhutan (Kawamoto, et al 2006) Myanmar, Bangladesh (Menon 2003, Chalise 2011) Thailand, and southernmost China and Laos (Zhou et al 2011, Timmins andDuckworth 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2010). Kawamoto et al (2006) recorded a pet Assamese macaque of unknown origin from Pakxe (15°07'N, 105°48'E), in the lowlands just west of the Bolaven plateau; but Pakxe is enough of a trading node that this should not be assumed to have been taken locally.…”
Section: General Distribution In Lao Pdrmentioning
confidence: 99%
“…Fooden's (1982) comprehensive review found most records from 150-1,900 m, with some up to 2,750 m (extended to 3,100 m by Fooden 1986), and a single, disjunct, record from sea-level (see below). A recent survey in Bhutan found Assamese macaques down to 600 m (Kawamoto et al 2006); Choudhury (2008) referred to occurrences as low as 100 m but neither detailed records traced by Fooden (1982Fooden ( , 1986 were almost solely in mid-and high-elevation forest, with the lower hill records coming from South Asia. Consistent with Fooden's (1982) conclusions, Ruggeri and Timmins (1997: 1) wrote that in the southern two-thirds of Lao PDR, "[Assamese macaque is] found predominantly in the evergreen forests of the Annamites [mountains]" but continued "it appears to be the most common species of macaque within areas of karst."…”
Section: Introductionmentioning
confidence: 98%